ANALYSIS OF DIGITAL MARKETING COMMUNICATION MIX STRATEGIES FOR INDOMIE PRODUCTS: MULTICHANNEL INTEGRATION FOR OPTIMIZING BRAND ENGAGEMENT AND CONSUMER LOYALTY - Romy Di Putra (RADJA PUBLIKA, 2026)
The development of digital technology encourages companies to adopt more integrated and multi-channel marketing communication strategies to maintain competitiveness amidst increasingly fierce market competition. This study aims to analyze the effectiveness of the digital marketing communication mix implemented by Indomie through the